The Globalisation of Chinese Food. - Cheung, Sidney (Anthropology of Asia., 2014)
By considering the practice of globalisation, these essays describe changes, variations and innovations to Chinese food in many parts of the world. The book reviews and broadens classic theories about ethnic and social identity formation through the examination of Chinese food, providing a powerful testimony to the impact of late 20th century globalisation.